Golgi apparatus analyzed by cryo-electron microscopy - Han, Hong-Mei; Grabenbauer, Markus (Histochemistry and cell biology, 2013)
In 1898, the Golgi apparatus was discovered by light microscopy, and since the 1950s, the ultrastructure composition is known by electron microscopic investigation. The complex three-dimensional morphology fascinated researchers and was sometimes even the driving force to develop novel visualization techniques. However, the highly dynamic membrane systems of Golgi apparatus are delicate and prone to fixation artifacts. Therefore, the understanding of Golgi morphology and its function has been improved significantly with the development of better preparation methods. Nowadays, cryo-fixation is the method of choice to arrest instantly all dynamic and physiological processes inside cells, tissues, and small organisms. Embedded in amorphous ice, such samples can be further processed by freeze substitution or directly analyzed in their fully hydrated state by cryo-electron microscopy and tomography. Even though the overall morphology of vitrified Golgi stacks is comparable to well-prepared and resin-embedded samples, previously unknown structural details can be observed solely based on their native density. At this point, any further improvement of sample preparation would gain novel insights, perhaps not in terms of general morphology, but on fine structural details of this dynamic organelle.
Gesehen am 25.02.2021